2008
DOI: 10.1007/s00213-008-1080-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of neuropeptide S in mice: therapeutic relevance to anxiety disorders

Abstract: These data provide an important confirmation and expansion of the anxiolytic-like effects of NPS and implicate the NPS system as a novel target for anxiolytic drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
116
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 39 publications
20
116
0
Order By: Relevance
“…This bias provided clear evidence that the hNPS-(1-10)-induced ERK1/2 phosphorylation had been attenuated by the G␣ q inhibitor UBO-QIC but not by the PKA inhibitor H89. Binding analysis using fluorescence-labeled NPS showed a similar activity in binding with the NPS receptor between WT NPS and NPS- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These data strongly suggest that the fragment hNPS-(1-10) activates signaling biased toward the G␣ q -coupled cascade over G␣ s -dependent cascade through the NPS receptor.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This bias provided clear evidence that the hNPS-(1-10)-induced ERK1/2 phosphorylation had been attenuated by the G␣ q inhibitor UBO-QIC but not by the PKA inhibitor H89. Binding analysis using fluorescence-labeled NPS showed a similar activity in binding with the NPS receptor between WT NPS and NPS- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These data strongly suggest that the fragment hNPS-(1-10) activates signaling biased toward the G␣ q -coupled cascade over G␣ s -dependent cascade through the NPS receptor.…”
Section: Discussionmentioning
confidence: 66%
“…These include the thalamus, hypothalamus, amygdala, and cortical areas (1,4,5). Upon central administration in rodents, NPS has been found to exert a variety of biological effects, including reduction of anxiety-related behavior (1,6,7), increase of locomotor activity (6,8,9), stimulation of wakefulness (1,6), inhibition of food intake (9,10), and enhancement of memory formation (11). Recent studies have also reported its involvement in the suppression of alcohol consumption (12,13) and in the extinction of contextual conditioned fear responses (14,15).…”
mentioning
confidence: 99%
“…After having ascertained that intranasally administered NPS reaches its target cells, we established its anxiolytic effects reported in intracerebral administration studies (Xu et al, 2004;Leonard et al, 2008) for this transnasal delivery method. In order to define the most efficient treatment dose, we delivered three different doses of NPS (7, 14, and 28 nmol) intranasally to C57BL/6N mice, a mouse strain reported to show reduced anxiety after ICV administration of NPS (Xu et al, 2004;Jüngling et al, 2008;Fendt et al, 2010).…”
Section: Intranasally Administered Nps Exerts Strong Anxiolytic Effecmentioning
confidence: 99%
“…The novel neuropeptide S (NPS) has been shown to elicit strong anxiolytic effects in rodents upon intracerebral injection (Leonard et al, 2008;Xu et al, 2004). NPS treatment facilitates fear extinction in mice and reduces fear memory retrieval after extinction training (Jüngling et al, 2008), thus becoming interesting especially for posttraumatic stress disorder (PTSD) treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation